An exploratory study of indirect ICT costs using the structured case method - Love, Peter; irani, Z.; Ghoneim, A.; Themistocleous, M. (Pergamon, 2006)
Many companies are increasing their expenditure on information and communication technologies (ICTs) to obtain or even sustain competitive advantage in their respective marketplaces. Many managers, however, are often left with the quandry of how to evaluate their investments in technologies. Reasons for this difficulty have been suggested in the normative literature as centring on the socio-technical (human, organisational and technical) dimensions associated with the adoption of ICTs. The inability of managers to determine the true costs of deploying ICT are considered attributable to a lack of knowledge and understanding of ICT-related costs. In developing a broader picture of such cost dimensions and their respective taxonomies, the research presented in this case uses a structured method to gain an understanding of how a construction firm embraced the information technollogy (IT) evaluation framework (CF) that focuses on indirect costs is proposed. Findings frm the case study are presented and discussed in the context of the CF.